О неоднородности стад рыбца — Vimba vimba natio carinata (Pall.) Дона и Кубани - Щербуха, А.Я. (Вестник зоологии, 1972)
Real differences are established in meristic and plastic characters between V. vimba natio carinata (P all.) populations from the Don and Kuban, which testify to their morphological heterogeneity. Individuals of both populations enter the rivers for reproduction at different time. Besides, the data on V. vimbo natio carinata (Pall.) catch in the Don and Kuban fishing regions of the Sea of Azov evidence for the presence of two V. vimba natio carinata P all. schools in it confined to the basins of the above-men-tioned rivers.